Legal Consequences of Differences in Value of Sale and Purchase Transac-tions on the Results of Verification of Land and Building Acquisition Fees - Eranda, Genta (IHSA Institute, 2024)
This study discusses the problems arising from the difference in transaction value stated in the deed of sale and purchase (AJB) with the results of the verification of Land and Building Acquisition Fee (BPHTB) by the Regional Tax and Retribution Management Agency (BPPRD) in South Lampung. The analysis was conducted using a qualitative approach, involving a literature study of the regulations governing BPHTB, as well as an analysis of cases and problems that arise in the field. The findings indicate that the practice of re-verifying prices by BPPRD can be detrimental to the parties involved in land/building sale and purchase transactions and violates the principle of freedom of contract in contract law. The implications of this problem are the potential for legal uncertainty and tax disputes between taxpayers and the local government. Therefore, further studies are needed to improve the implementation of BPHTB collection policies in South Lampung and increase public understanding